Respuesta :

To determine this, the first thing we should do is simplify the expression. As usual, bring like terms to either side of the "=" and then simplify.
2x + 6 - x = 1/3 (3x + 18)
x + 6 = 1/3 (3x + 18)
x + 6 = 1/3 (3x) + 1/3(18)
x + 6 = x + 6

We can already see that both sides have the same expression "x+6". Now, if you try to simplify any further, you will get 0=0. That means that for any value of x, the expression will simplify to 0=0. Because 0=0 is a true statement, for every value of x, the expression will be true. Therefore, there are an infinite number of solutions.

Hope this helped!! :D
Note: If you are still confused, let me know. I realize that I might have been a bit confusing in my explanationÂ